2014
DOI: 10.1590/s0100-69912014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-level laser therapy on wound healing

Abstract: Low-level laser can be safely applied to accelerate the resolution of cutaneous wounds, although this fact is closely related to the election of parameters such as dose, time of exposure and wavelength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 24 publications
1
44
0
22
Order By: Relevance
“…Another study 7 showed that the LPL (InGaAlP, 660 nm, According to literature, doses ranging from 3-6 J/cm 2 appear to be more effective, while doses higher than 10 J/cm 2 are associated with harmful effects 13 , nevertheless, it was proved that a daily dose of 30 J/cm 2 and power density at 25 mW/cm 2 of 670 nm laser, continuous mode, was able to shorten the inflammation without compromising the metabolism of fibroblasts, positively influencing all the phases of wound cicatrization in the skin of 49 rats, which produced two parallel wounds on the back, where one served as a control and the other was exposed to laser irradiation 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study 7 showed that the LPL (InGaAlP, 660 nm, According to literature, doses ranging from 3-6 J/cm 2 appear to be more effective, while doses higher than 10 J/cm 2 are associated with harmful effects 13 , nevertheless, it was proved that a daily dose of 30 J/cm 2 and power density at 25 mW/cm 2 of 670 nm laser, continuous mode, was able to shorten the inflammation without compromising the metabolism of fibroblasts, positively influencing all the phases of wound cicatrization in the skin of 49 rats, which produced two parallel wounds on the back, where one served as a control and the other was exposed to laser irradiation 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, several studies have shown the benefits of the extensive use of the LPL in situations such as the treatment of soft tissue injuries, joint diseases, open wounds, pressure ulcers, among others [11][12][13][14] . The AlGaInP laser (660 nm) is a therapeutic light of the electromagnetic spectrum in the red line, whose irradiation in injured tissues triggers a series of physiological effects necessary for the process of wound cicatrization and repair at tissue and organic levels by means of the photobiomodulation process, in addition to causing therapeutic effects, such as: local analgesia, edema reduction and anti-inflammatory action 11,15 .…”
Section: Led (Light Emitting Diode) and The High Frequency Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using LLLT showed no similarities due to changes in methodology due to differences in implemented radiation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the latest technologies is the low-level laser, which has characteristics to induce cell proliferation, increase the ATP synthesis, increase tensile strength of scar tissue and promoting the reduction of pain and trauma during dressing change [4][5][6][7][8] . There are currently promising research aiming to substantiate the benefits of laser therapy as well as the occlusive dressing in moist environment in the systemic healing process of a wound 4,6,7,9,10 . Thus the present study evaluated the effects of low-level laser associated with the hydrocolloid dressing on wound tissue repair in rats, by assessing the diameter of the wound and the histological analysis of healing.…”
Section: Introductionmentioning
confidence: 99%